Albumin-to-alkaline phosphatase ratio may be a better predictor of survival than sclerostin, dickkopf-1, osteopontin, osteoprotegerin and osteocalcin - K. Mathold; R. Nobin; L. Brudin; M. Carlsson; P. Wanby (Heliyon, 2024)
Objectives: The value of biochemical markers of bone turnover (BTMs) in predicting survival and disease remains unclear. In a prospective study we evaluated the novel biomarkers for bone turnover sclerostin, dickkopf-1 (DKK-1), osteopontin (OPN), osteoprotegerin (OPG) and osteocalcin (OC), as well as a traditional biomarker, alkaline phosphatase (ALP) in relation to risk of mortality, cardiovascular events and fractures. Participants: and Methods:Routine blood tests and serum BTMs, including ALP, were analyzed in patients with hip fracture n = 97, stroke n = 71 and healthy volunteers n = 83 (mean age 86, 83 and 77, respectively), followed for 7 years. Hazard Ratios (HR) were calculated for mortality, cardiovascular events and fractures in relation to these biomarkers. After adding the albumin-to-ALP ratio (AAPR) a post hoc analysis was performed. Results: 120 participants died during the study. In the entire group of patients and volunteers (n = 251) higher AAPR (HR 0.28, 95 % CI 0.14–0.59, p < 0.001) was associated with decreased mortality. OPN and OPG were associated with mortality risk only in the univariate statistical analysis. HR for high AAPR in relation to new cardiovascular events was borderline significant (HR 0.29, 95 % CI 0.08–1.06, p = 0.061). None of the examined biomarkers were associated with new fractures, nor with an increased risk of a new cardiovascular event. Conclusions: AAPR may be a better predictor of mortality than the more novel BTMs, and higher AAPR could be associated with longer life expectancy. Further studies should determine the clinical usefulness of AAPR as a biomarker of mortality and cardiovascular disease.